Classroom Experiments using Phytochemical Analysis of Weed (Eleusine Indica) - Malaguial, Princes Aires; Maggay, Althea Kate; Sibugan, Brad Van; Salaban, Querbenz; Abusama, Hassanal (Universitas Pendidikan Indonesia (UPI), 2021)
This study aimed to demonstrate simple classroom experiments by evaluating the phytochemical components of the extracts of weed (Eleusine indica). The purpose of this study is also to contribute effective use of natural resources in the locality by transforming traditional knowledge to the scientific way of using the medicinal plant to be used as raw materials in pharmaceutical industries. The weed was air-dried for ten days. It was then pulverized using an electric blender. The mixtures were allowed to stand for seventy-two hours to extract the bioactive components of the weed. The experiment used chloroform (polar) in extracting the secondary metabolites present in the weed.Â Â The mixtures were then filtered with a cheese cloth and concentrated in direct heat using a hot plate. The extract was placed in a beaker and was labelled as chloroform extract. The bottle was covered tightly to prevent evaporation of the solvent. The Phytochemical components present in the weed extracts were alkaloids, flavonoids, carbohydrates, diterpenes, and saponins. This study is expected to be one of the teaching model (since the experiments are simple). This study also is expected to identify the phytochemical components of weed, identify the phytochemical components of weed, and contribute to the effective use of natural resources.